Konsumsi Energi Fosil Terhadap Pertumbuhan Ekonomi - Devia Septyani; Sri Hartati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The research aims to determine the correlation between fossil energy consumption and economic growth in Indonesia. The data uses in this research was a 6-year period, of secondary data, starting form 2018 to 2023, obtained from the Ministry of Energy and Mineral Resources (ESDM) for the fossil energy consumption variable and the Central Statistics Agency (BPS) for the economic growth variable. The analytical method used in this research was simple linear regression analysis using SPSS 24 software tools. The research results showed that fossil energy consumption had a positive effect in Indonesia economic growth. The research indicated that fossil energy consumption was able to increase Indonesian economic growth by 64,7%. Keywords: energy consumption (fossil), economic growth